Gendered Performances in Social Media Promotions for English Learning - Virda Rizki Ananda; Didin Nuruddin Hidayat; Nida Husna (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2026)
This study explores how gender is represented in English language education promotions on social media, focusing on Instagram content by @kampunginggrislc, a well-known English course provider in Pare, Indonesia. Using a qualitative approach and Critical Discourse Analysis (CDA) based on Fairclough’s model and Judith Butler’s theory of gender performativity, this research investigates six selected video posts. The findings show that male and female figures are portrayed differently in both verbal and visual elements. Male speakers are often positioned as authoritative and logical, while female speakers are associated with emotional, polite, and aesthetic values. These gendered performances reflect broader cultural expectations in Indonesian society. The study concludes that English language promotional content on social media not only serves educational purposes but also functions as a space where gender ideologies are reproduced and normalized. The research calls for greater awareness in creating inclusive educational media that supports gender equality.